Myocarditis following COVID-19 vaccination in adolescents: Cardiac magnetic resonance imaging study - Arthur Shiyovich; Ygal Plakht; Guy Witberg; Amichai Rotstein; Yaron Aviv; Maya Wiessman; Ran Kornowski; Ashraf Hamdan (Frontiers in Cardiovascular Medicine, 2022)
IntroductionVaccination-associated myocarditis was reported following COVID-19 vaccine initially among persons aged 16 or older and recently among adolescents aged 12–15.ObjectivesTo describe the clinical and cardiac magnetic resonance (CMR) characteristics of adolescents aged 12–15 with myocarditis following the administration of the BNT162b2 mRNA COVID-19 vaccine.MethodsCMR of adolescents (age 12–15) with a clinical diagnosis of myocarditis within 42 days following the first COVID-19 vaccine were analyzed.ResultsA total of 182,605 adolescent were vaccinated, out of which 9 were diagnosed with clinically adjudicated myocarditis while CMR was performed in 5/9 patients (56%). Median age was 15 years (range 13–15), 4/5 (80%) males. All the patients we previously healthy. The ECG upon presentation was abnormal in 3/5 (60%) of patients. All cases were classified as clinically mild and no patient required inotropes or mechanical circulatory support treatment. The median follow-up time, for the 5-included patients, was 206 (IQR 192–229, range 179–233) days. During the follow-up, no re-admissions, deaths, or any other cardiac events have occurred.The median time between the diagnosis to the CMR was 104 days (range 27–149). The median left ventricular ejection fraction was within normal range 65% (range 62–69). Native T1 was available in four patients, the local T1 value was increased in three of them. T2 values were available in two patients and were all within normal range. The median late gadolinium enhancement (LGE) was 2% (range 0–6%) with inferolateral wall being the most common location (3/5). The patterns of the LGE were as following: (i) mid-wall in 3 patients; (ii) epicardial in 1-patient. LGE in the pericardium was present in 2/5 patients with pericardial effusion present in 4/5 patients with a median diameter of 4 mm (range 3–5 mm) at end-systole.ConclusionsCMR findings and clinical course of adolescents with COVID-19 vaccination associated myocarditis, are similar to those of older patients, being relatively mild and potentially implying favorable outcomes.